Translation, cross-cultural adaptation and validation of the Chinese version of supportive and palliative care indicators tool (SPICT-CH) to identify cancer patients with palliative care needs - Zhishan Xie; Siyuan Tang; Claire E. Johnson; Lin Xiao; Jinfeng Ding; Chongmei Huang (BMC Palliative Care)
Abstract Introduction People diagnosed with cancer are the most frequent users of palliative care. However, there are no specific standards for early identifying patients with palliative care needs in mainland China. The Supportive and Palliative Care Indicators tool (SPICT) can identify patients with cancer who are in need of palliative care across healthcare settings. Objective To translate, cross-cultural adapt the SPICT and validate it among cancer patients with palliative care needs in a Chinese healthcare context. Method We translated and culturally adapted the SPICT from English into Chinese, following both Beaton’s and WHO’s recommendations: (1) initial translation, (2) synthesis, (3) back translation, (4) expert committee review, and (5) pretest. The psychometric properties (e.g., content validity, internal consistency, and inter-rater reliability) were analyzed. Convenience sample was used to recruit 212 hospitalized cancer patients between January and August 2023. Their needs were assessed by two nurses within 24hours to determine the inter-rater reliability and stability of the Mandarin version of SPICT (SPICT-CH). Results All of 36 items were retained in response to expert review. The Scale-Content Validity Index/Ave (S-CVI/Ave) of the SPICT-CH was 0.98, demonstrating very strong content validity. The SPICT-CH exhibited good coherence (Cronbach’s alpha = 0.76) and reliability (Kappa = 0.71, 95% CI 0.71-0.72, P < 0.05). Conclusion The SPICT-CH has good content validity and acceptable reliability among cancer patients within a Chinese hospital setting. This instrument can be effectively integrated into routine clinical practice to early identify patients who need palliative care in mainland China.